Fructose intake and its association with relative telomere length: an exploratory study among healthy Lebanese adults - Messerlian, Nairie; Zgheib, Nathalie; Chokor, Fatima Al Zahraa; Nasrallah, Mona; Tamim, Hani; Nasreddine, Lara (Frontiers in Nutrition, 2023)
Shorter relative telomere length (RTL) has been associated with increased incidence of morbidity. Although still disputed, available evidence suggests that dietary factors, including sugar-sweetened beverages (SSB) may be linked with shorter RTL. It was argued that the link between SSB and RTL may be explained by the sugar content of these beverages, and specifically fructose given its impact on oxidative stress and the inflammatory response. However, none of the existing studies have examined the specific link between fructose intake and RTL. This exploratory study aimed at (1) assessing the intake of dietary fructose (total, added and natural) in Lebanese healthy adults and (2) examining dietary fructose as a predictor of short telomere length. Following a cross-sectional design (n=282), anthropometric and biochemical data were collected. RTL was assessed by utilizing real-time polymerase chain reaction (RT-qPCR) to amplify both telomere and single-copy gene segments. Dietary intake was evaluated using a culture-specific food frequency questionnaire (FFQ). Intakes of added fructose, naturally-occurring fructose, and total fructose were estimated. Mean intakes of added and natural fructose were of 39.03 ± 34.12 g/day and 12.28 ± 8.59 g/day, respectively, representing 4.80 ± 3.56 % and 1.78 ± 1.41% of total energy intake (EI). Mean total fructose intake was of 51.31 ± 35.55 g/day, contributing 6.58 ± 3.71% EI. Higher intakes of total and added fructose were significantly associated with shorter RTL (2nd RTL tertile as compared to the 3rd RTL tertile; relative risk ratio (RRR)=3.10 (95% confidence interval (CI): 1.38, 6.94) and RRR=2.33 (95%CI: 1.02, 5.36), respectively) after adjustment for confounders identified using a directed acyclic graph (DAG). In conclusion, although we could not observe a dose-dependent relation between fructose intakes and RTL shortening and although the study is limited by its small sample size, the findings suggest that total and added dietary fructose intakes may be associated with shorter RTL. Larger studies, of longitudinal nature, are needed to further confirm the study findings.